Revitalizing shrimp cultivation in Kolaka Regency, Southeast Sulawesi through IoT water quality monitoring to increase productivity - Nuryadi, Ahmad Muhlis; Hamka, Eddy; Fajriani , Alfiah; Sulisworo, Dwi; Maryani, Ika; Erviana, Vera Yuli (Universitas Ahmad Dahlan, 2023)
This paper describes a community empowerment program by implementing Internet of Things (IoT) Water Quality Monitoring technology to encourage innovation and increase productivity in shrimp cultivation. Collaboration between Muhammadiyah University of Kendari, Ahmad Dahlan University, and local farmers has resulted in the latest solution to optimize shrimp pond management. This empowerment involves a series of stages, from identifying water quality problems to implementing IoT monitoring infrastructure in the field. First, through intensive discussions, critical issues faced by farmers were identified. Based on these findings, the development team from Ahmad Dahlan University designed and implemented a solution in the form of IoT Water Quality Monitoring. Furthermore, the Muhammadiyah University of Kendari held intensive training and workshops to increase farmers' understanding of data interpretation and tool operation. The workshop lasted for three days, which successfully improved farmers' practical skills and increased optimism regarding increasing shrimp production. The final stage of this empowerment involves installing IoT Water Quality Monitoring infrastructure at identified shrimp farming locations. In conclusion, implementing this technology significantly positively impacts shrimp cultivation productivity and farmer welfare. Recommendations for further development and wider dissemination of information provide a basis for improving sustainability and efficiency in the local fisheries sector.